Estudo post mortem através da técnica do pink teeth em vítimas de mortes violentas em Curitiba e Região Metropolitana - Gavrilko, Oleg (2013)
Pink teeth are a phenomenon that can occur in life or post-mortem. It is resulted by pigmentation tooth by hemoglobin, which diffuses through the dentinal tubules. Several researches have analyzed this phenomenon, in order to elucidate its mechanism and try to relate to the cause of death and the time elapses from death, to assist and make faster the word of criminal investigation in discovering the real situation of death. In this work the author tried to correlate the appearance of the pink teeth with time and cause of death, measuring the color. Were conducted a field study at the Institute of Forensic Medicine of Curitiba, where were analyzed 15 specimens with different causes of death. For the staining was used to measure the color gamut of RGB Hex Triplet Color Char and held visual comparison of the teeth. It was verified that the teeth of the battery lip, i.e. from canine to canine were the most affected teeth and the neck of the teeth – or the tooth neck region of the cementum-enamel junction, or neck of the tooth, it shows one more exuberant color. Is proposed the development of a electronic colorimeter as future work, with the subject to automate the capture the color in the pink teeth.